Indoor air quality (IAQ) in preschools and its association with respiratory inflammation among pre-schoolers - Zainudin, Muhammad Akid; Jalaludin, Juliana; Sopian, Nor Ashikin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Children spend most of the time indoors and make them easily exposed to indoor air contaminants. Exposure to poor indoor air quality has led to various health problem especially, respiratory-related illness. This study is intended to determine the relationship between indoor air pollutants exposure and the airway inflammation among children aged 5 to 6 years old in selected preschools from mid-2015 until mid-2016. Methods: Four hours of indoor air quality assessment had been conducted at six preschools in Puchong district (urban area) and six preschools in Hulu Langat district (suburban area) of Selangor. The respiratory inflammation among 120 healthy preschool children had been assessed using non-invasive biomarker of Fractional Exhale Nitric Oxide (FeNO). Meanwhile, respiratory symptoms and information on possible residential air pollutant exposures were obtained from a standardized questionnaire. Results: The indoor air quality measurement demonstrated significant high concentration air pollutants (PM0.1, PM2.5, PM10, VOCs) at the preschools in the urban as compared to preschools in the suburban area(p < 0.05). Besides, PM2.5 was found to be significantly associated with respiratory inflammation (FeNO value) measured (p<0.05). Conclusion: The exposure of PM0.1, PM2.5, and PM10 had increased occurrences of respiratory inflammation and respiratory symptoms among susceptible populations like children.